Conceptual Model to Determine Maximum Activity of Radioactive Waste in Near-Surface Disposal Facilities - Iarmosh, I.; Olkhovyk, Yu. (Ядерна та радіаційна безпека, 2016)
For development of the management strategy for radioactive waste (RW) to be placed in near-surface disposal facilities (NSDF), it is necessary to justify long-term safety of such facilities. Use of mathematical modelling methods for long-term forecasts of RW radiation impacts and assessment of radiation risks from radionuclides migration can help to resolve this issue. The purpose of the research was to develop the conceptual model for determining the maximum activity of RW to be safely disposed in the NSDF and to test it in the case of Lot 3 Vector NSDF (Chernobyl exclusion zone). This paper describes an approach to the development of such a model. The conceptual model of ⁹⁰Sr migration from Lot 3 through aeration zone and aquifer soils was developed. The results of modelling are shown. The proposals on further steps for the model improvement were developed.